Application of voltammetric sensors to the determination of chloride in sea sand and cement pastes - HODOUCHI, Kazunori; YAMADA, Akifumi; KATOH, Yoshikiyo; KATOH, Koichi (BUNSEKI KAGAKU, 1987)
Voltammetric sensor with a small silver electrode (0.3 mm in diameter and 99.99% in purity) has been applied to the analysis of chloride in sea sand and cement pastes. The voltammetric sensor consisted of a silver electrode (working electrode), a lead/lead(II) sulfate electrode (reference electrode) and a stainless-steel electrode (counter electrode). The sensor was connected to the voltammetric analyzer. Alumina of various particle size (0.05, 1 and 8μm) was used to polish an electrode surface; well-reproduced currents were obtained at the polished electrode with 8 μm alumina in a concentration range of 0.051.0% of chloride. Pretreatment of the electrode for the electrochemical activation was also examined; good results were obtained in 2% NaCl solution. For the determination of chloride in sea sand, a 30 g of sea sand was added in 50 ml of water, and the mixture was agitated for 10 min in order to extract chloride. An aliquot was then added into 0.1 mol dm-3 NaNO3 solution and the current due to chloride was measured. Chloride content was also determined by Mohr method; a correlation between the results of voltammetric and Mohr methods was found to be excellent with a correlation factor of 0.994. As for the analysis of chloride in cement paste, cement paste was filtered by aspirator, and a portion of the filtrate was added into 0.1 mol dm-3 phosphate buffer (pH 7.0) or acetate buffer (pH 4.6) solutions. Tast polarogram of the combined solution was measured; concentration of chloride was determined from the electric current due to the oxidation of chloride. Chloride in cement paste was also determined by the Mohr method; the results were in excellent agreement with those obtained by the voltammetric method and a correlation factor was 0.994. Effect of a water-cement ratio on the determination of chloride content was examined; the variation of the current was ±2.3%, while the water-cement ratio varied from 0.56 to 1.67.